2012
DOI: 10.1177/1934578x1200700822
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Combretastatin A-4 and Three Combretastatin-Based Hybrids

Abstract: The syntheses of combretastatin A-4 from gallic acid and of three combretastatin-based hybrids are described. Starting from commercial gallic acid, the phosphonium salt (3,4,5-trimethoxybenzylphosphonium bromide) is synthesized and coupled, through a Wittig reaction, with several aldehydes, including methoxymethyl-protected isovanillin, the aldehyde γ-bicyclohomofarnesal having a labdane skeleton, 3-(3-pyridyl) propanal, and furfural. The biological properties of the cis-coupled compounds as cytotoxic, antivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…CA-4 and hybrid 9 revealed activities against HHV-1, and HHV-2. The antiviral activities of CA-4 against HHV-1, and HHV-2 are 50 and 25 µg/mL, respectively [38].…”
Section: Antimicrobial and Leishmanicidal Activitiesmentioning
confidence: 99%
“…CA-4 and hybrid 9 revealed activities against HHV-1, and HHV-2. The antiviral activities of CA-4 against HHV-1, and HHV-2 are 50 and 25 µg/mL, respectively [38].…”
Section: Antimicrobial and Leishmanicidal Activitiesmentioning
confidence: 99%
“…The determination of the reduction factor (R f ), which corresponds to the value obtained by dividing the viral titer in the absence of compound over the viral titer obtained in the presence of compound was employed as an end point of this antiviral bioassay (Table 3). 34 In a previous study carried out in our laboratory, 32 we reported the antiviral activity of combretastatin A-4 hybrid of HHV-2 at concentrations below 25.0 and 3.1 µg mL -1 . This background is important and establishes a guide for continue exploring antiviral activity.…”
Section: Resultsmentioning
confidence: 94%
“…31 We have found in previous studies that some CA-4 1 hybrids containing the (Z)-2-(3,4,5-trimethoxystyryl) furan moiety have showed interesting antifungal activity against T. mentagrophytes and T. rubrum, giving MIC values of 15.7 ± 6.8 and 15.8 ± 6.5 µg mL -1 , respectively. 32 Furthermore, the antifungal activity of 10c was previously determined against C. albicans ATCC 90028 giving an MIC value of 32.0 µg mL -1 . 33 The results of this study confirm that the 3,4,5-trimethoxy phenyl moiety should be the fragment, which improves the antifungal activity, especially against T. mentagrophytes, allowing to conclude that this pharmacophoric subunit of CA-4 1 is also relevant for the development of novel antidermatophytes agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combretastatin‐based hybrid 45 (Figure ) and its analogues were tested in vitro for potential antitumor and cytotoxic activities on HeLa tumor cell line and non‐tumor Vero cell line. This derivative showed a high potential antitumor activity with an IC 50 value in the low micromolar range …”
Section: Synthetic Anticancer Stilbenesmentioning
confidence: 99%